Perancangan Dudukan Motor Circulating Water Pump (CWP) Menggunakan Metode Elemen Hingga - Muhammad Iskandar; Mohamad Hakam; Heroe Poernomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
PT X. which is engaged in fabrication, has a CWP motor mount fabrication project with static and dynamic loads of 28,117 Kg. The design is carried out with a structural strength analysis intended to calculate the maximum moment, von mises stress, and deflection. This can affect the productivity of the company. This study aims to determine the value of von mises stress that occurs below the allowable stress. With manual calculation, the maximum von mises stress value on the CWP structure is 32.094 Mpa with a maximum deflection value of 0.323 mm. The maximum von mises stress value of manual calculation is below the permit stress and meets the permit stress requirement with a value of 100 Mpa. So the designed holder is categorized as very good.